Потребительская кооперация: назначение, структура, полномочия - Ищенко, А.Д.; Ячменева, В.М. (Культура народов Причерноморья, 2014)
Проведен ретроспективный анализ для выявления ключевых моментов формирования
концепции потребительской кооперации на основе законодательных актов, определили понятие
потребительской кооперации, используя логику и анализ факторов, выявили потребности субъектов
потребительской кооперации и сгруппировали их по классификационным признакам. Используя
системный подход и метод дедукции, определили субъекты потребительской кооперации. Проведено ретроспективний аналіз для виявлення ключових моментів формування концепції
споживчої кооперації на основі законодавчих актів, визначили поняття споживчої кооперації,
використовуючи логіку і аналіз чинників, виявили потреби суб'єктів споживчої кооперації та згрупували
їх за класифікаційними ознаками. Використовуючи системний підхід і метод дедукції, визначили
суб'єкти споживчої кооперації. A retrospective analysis to identify the key points of the formation of the concept of consumer
cooperation on the basis of legislation and determined that in 1844 registered the first co-op «Society honest
pioneers» through the procedures of institutions, adoption of regulations and empowerment of consumer
cooperatives, in 1917, was formed Central Union of Consumer Societies of Russia and it was he who laid the
foundation for the entire cooperative movement. The new era of consumer cooperatives began in 1991 in a
completely new environment of formation of the Russian economy. Complete formation of consumer cooperatives was due to the adoption of legislative acts and powers that have been identified сconsumer
сoperatives. Also defined the concept of the modern consumer cooperation as cooperation resources, natural
and legal persons with capacity for innovation, providing socio-oriented production, the development of
innovation and innovation management system. Using logic and analysis of the factors identified needs of the
subjects of consumer cooperatives and grouped them according to the classification criteria. Thus, the needs of
subjects of consumer cooperatives were organized into groups: economic, social, legal, educational and
environmental. Using a systematic approach and the method of deduction, identified the subjects of consumer
cooperatives, which are members of consumer societies, shareholders, employees of enterprises and
organizations and consumers of goods and services of consumer cooperatives and their interests.